Tea Scale, Fiorinia theae Green (Insecta: Hemiptera: Diaspididae) - Christian F. Miller (EDIS)
This document provides a detailed overview of the tea scale, Fiorinia theae, an insect pest native to Asia and now found in various parts of the world, including the southeastern United States. It covers the insect's distribution, life cycle, physical characteristics, and economic significance, particularly its impact on ornamental plants like camellias and hollies. The article also discusses management strategies, including cultural, chemical, and biological controls, to mitigate the pest's impact. This document is part of the UF/IFAS Extension's Featured Creatures collection, aimed at both laypersons and academic audiences interested in entomology. First published: November 2001.